The Use of Translation Procedures and Resulted Errors in Students’ English-Indonesian Translation Paper Abstract (The Journal of Educational Development, 2021)
For non-native speakers to understand the meaning of the English text, the text must be translated since English is a widely spoken language with a wide variety of purposes. This study aims to find out the translation procedures used by students in translating paper abstracts from English to Indonesian translation and to identify the errors resulting from students' English-Indonesian translation of paper abstractions. This study uses a qualitative research design, particularly the descriptive qualitative method. The result showed that students use eight translation procedures—Couplet, Literal Translation, Triplet, Modulation, Paraphrase, Transposition, Compensation, and Reduction. Then, Couplet is the most dominant translation procedure used by students, with a 54.6% percentage, and the minor translation procedure is Reduction, with a 0.2% percentage. The translation errors result showed that students made eight translation errors. They are Errors of spelling, Errors of grammar, syntax, Inappropriate register, Error of punctuation, Distortion, Unidiomatic expression, Unjustified insertion, and Unjustified omission. Errors of Spelling the is the most dominant errors made by students, with a 43.6% percentage, and the minor translation error is Unjustified omission, with a 2.3% percentage. Therefore, translation procedures and translation errors are essential in the translation process.